Stuttgart 21 - Kostensprünge und Verzögerungen. Warum der Bahnhof immer noch nicht unter der Erde ist. - Burgdorf, Christian (Deutscher Verkehrs-Verl., 2009)
Bei Großprojekten gehören Verzögerungen und Kostensprünge zu den regelmäßigen Begleiterscheinungen - auch bei Stuttgart 21. Eine Analyse der Planungsphase des baden-württembergischen Mammutprojekts hat gezeigt, welche Ursachen bisher dafür verantwortlich waren.

The investigation deals with the phenomenon that, in the case of large-scale transport infrastructure projects, delays and cost overruns tend to be a regular occurrence. A risk analysis that covers the planning phase of the 'Stuttgart 21' project has identified the causes responsible for deviations from given targets. In particular, risky project financing and a generally inept public sector have, coupled with project partners' fairly reserved attitude towards their involvement with this venture, prevented a timely completion. Furthermore, the excessively long time taken to define the process of project planning has contributed to an extension of the planning stage.
Project Stuttgart 21.
Keywords: Öffentlicher Verkehr; Schienenverkehr; Bahnhof; Hauptbahnhof; Verkehrsbauwerk; Verkehrsinfrastruktur; Planfeststellungsverfahren; Investitionskosten; Risikoanalyse; Ursachenanalyse; Großprojekt; Verzögerung; Kostensteigerung